A coupled hydro-sediment-ecological modeling approach to simulating ecological dynamics in the large reservoir system of Southwest China - Longhu Yuan; Jiamei Zhang; Yuning Tan; Huaixiang Liu; Yubin Chen; Yongjun Lu; Zhili Wang (CATENA, 2026)

Contamination profiles of legacy and emerging per- and polyfluoroalkyl substances in various vegetable oils collected in Chinese markets - Wenfeng Feng; Yuepeng Lu; Yuning Hu; Jing Cheng; Ling Wang; Zhen Zhou; Yong Liang (Journal of Environmental Sciences, 2026)

Evolution of pore structure and fractal characteristics during hydrate-based CO2 sequestration in unconsolidated sediments - Zhun Zhang; Yuning Liu; Yunkai Ji; Jiaxian Wang; JinQiu Hu; Bin Fang; Wanjun Lu; Changling Liu; Fulong Ning (Chemical Engineering Journal, 2026)

On-site detection of tobramycin using low-cost and ultrasensitive ratiometric fluorescence sensing platforms based on S,N-co-doped dual emission carbon quantum dots - Chumeng Wang; Yuning Chen; Nengsheng Ye; Lu Zhang; Yuhong Xiang (Analytica Chimica Acta, 2026)

Molecular Insights into Exoskeletal Remodeling: Transcriptomic Profiling of the Molting Cycle in the Red Swamp Crayfish Procambarus clarkii - Yunkuan Zhu; Yu Xu; Suwan Lu; Yuning Hu; Hui Xu; Jiajia Li; Hai Lin; Xuguang Li; Zhiqiang Xu (Fishes, 2026)
The molting of crustaceans is accompanied by exoskeleton reconstruction. To reveal the molecular regulation mechanism of exoskeleton remodeling, the transcriptomic profiles of the exoskeleton across the entire molting process in the red swamp crayfish Procambarus clarkii were investigated by RNA sequencing, yielding a total of 7671 differentially expressed genes (DEGs) across five different molting stages. Notably, the key DEGs were those related to cuticular exoskeleton synthesis (cuticular proteins), degradation (chitinase 2, chitinase 10) and hardening (chitin deacetylase 1), and their expression abundance varied by 10-fold or greater across the molting cycle. Analysis of Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) showed that significantly enriched pathways included the structural constituents of the cuticle, structural molecule activity, chitin binding of chitin metabolism, and hormone biosynthesis. The expression profiles of nine selected molting-related DEGs were further validated via real-time RT-PCR assays. The acquired unique temporal expression patterns involved in exoskeleton remodeling provide a preliminary insight into the regulation of gene expression during the molting cycle in the red swamp crayfish.

Identification of the geographical origin of wild rice field eel (Monopterus albus) in China by stable isotopes - Weiwei Lv; Muyan Li; Yangyang Lu; Yifan Zhao; Weiwei Huang; Hang Yang; Quan Yuan; Yuning Zhang; Mingyou Li; Wei Hu; Chunxia Yao; Danhe Wang; et al. (Food Control, 2026)

Single-cell RNA sequencing reveals the heterogeneity of hepatopancreas cells and their association with gonadal development in the red swamp crayfish Procambarus clarkii - Lin Du; Yuning Hu; Siyu Lu; Xuguang Li; Jiajia Li; Hai Lin; Jiaxin Yang; Yu Xu; Zhiqiang Xu (Aquaculture, 2025)

Assessing thermal comfort for the elderly in historical districts and proposing adaptive urban design strategies: A case study in Zhenjiang, China - Yingnan Li; Yuhan Zhang; Yuedong Wang; Zipeng Song; Zhicheng Zhou; Lu Ding; Cen Chen; Xi Jin; Yuning Cheng (Landscape and Ecological Engineering, 2025)

Epithelial-mesenchymal transition during the growth and involution of the prostate gland in wild ground squirrels (Spermophilus dauricus) - Pengyu Chen; Xinyue Hu; Qingjing Gao; Yue Zhou; Wenjing Lu; Xingye Zhang; Maria Daniela Artigas Ramirez; Yingying Han; Zhengrong Yuan; Yuning Liu; Qiang Weng; Haolin Zhang (Animal Reproduction Science, 2025)

Milk-derived small extracellular vesicles: a new perspective on dairy nutrition - Yuning Zhang; Yingying Lin; Jian He; Sijia Song; Yujia Luo; Yao Lu; Shuxing Chen; Qingyu Wang; Yixuan Li; Fazheng Ren; Huiyuan Guo (Critical Reviews in Food Science and Nutrition, 2024)

MFNet: Multi-scale feature enhancement networks for wheat head detection and counting in complex scene - Yurong Qian; Yugang Qin; Hongyang Wei; Yiguo Lu; Yuning Huang; Peng Liu; Yingying Fan (Computers and Electronics in Agriculture, 2024)

LbCOPT1 is a copper transporter induced in Lycium barbarum mycorrhizal roots, which allows tobacco with improved growth and nutrient uptake - Yuhao Zhou; Yuning Li; Jingru Jia; Yinjun Lu; Beijia Feng; Ming Tang; Haoqiang Zhang (Plant Cell Reports, 2024)

Novel cow dung-doped sludge biochar as an efficient ozone catalyst: Synergy between graphitic structure and defects induces free radical pathways - Yuxuan Yang; Kedong Ma; Yubo Cui; Ke Zhao; Yuning Lu; Wanjun Zhang; Peijing Kuang; Xuejun Zou (Environmental Research, 2024)

ENSO-driven hydroclimate changes in central Tibetan Plateau since middle Holocene: Evidence from Zhari Namco’s lake sediments - Changrun Wu; Guangxin Liu; Lu Cong; Xiangzhong Li; Xiangjun Liu; Yuning Liu; Deyan Wu; Yuyan Zhang; Die Bai (Quaternary Science Reviews, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

A survey of deep learning-based object detection methods in crop counting - Yuning Huang; Yurong Qian; Hongyang Wei; Yiguo Lu; Bowen Ling; Yugang Qin (Computers and Electronics in Agriculture, 2023)

Sediment yield in the Lower Jinsha River Basin, China: Controlling factors and spatiotemporal patterns - Yuning Tan; Huaixiang Liu; Yongjun Lu (CATENA, 2023)

Interplay of flow and bed morphology caused by pool-riffle sequence formation without upstream sediment supply in gravel-bed rivers - Jiyi Gu; Huaixiang Liu; Yongjun Lu; Tingjie Huang; Yuning Tan; Mingcheng Zhu (CATENA, 2023)

Occurrence of halogenated methanesulfonic acids in water and sediment from the Hangzhou Bay, China - Fang Tao; Yujia Tan; Junwei Dai; Congrui Lu; Yadong Sha; Yi Liu; Xinxing Zhou; Qingele Hasi; Zhemin Shen; Yuning Ma (Environmental Research, 2023)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Slag discharge characteristics and engineering application of prismatic grooved drill pipe in borehole collapse - Yonglong Wang; Zaijiang Yu; Zhenfeng Wang; Yuning Sun; Bo Lu; Weiyong Lu; Dingding Guo (Arabian Journal of Geosciences, 2022)

Skeletal abnormalities and extra-skeletal ossification in mice with restricted Gsα deletion caused by a renin promoter-Cre transgene - Hayo Castrop; Mona Oppermann; Diane Mizel; Yuning Huang; Robert Faulhaber-Walter; Yvonne Weiss; Lee S. Weinstein; Min Chen; Stephane Germain; Huiyan Lu; Dan Ragland; Daniel M. Schimel; et al. (Cell and Tissue Research, 2007)